1997
DOI: 10.1017/s0954579497001430
|View full text |Cite
|
Sign up to set email alerts
|

Representations of self and other in the narratives of neglected, physically abused, and sexually abused preschoolers

Abstract: The MacArthur Story Stem Battery was used to examine maternal and self-representations in neglected, physically abused, sexually abused, and nonmaltreated comparison preschool children. The narratives of maltreated children contained more negative maternal representations and more negative self-representations than did the narratives of nonmaltreated children. Maltreated children also were more controlling with and less responsive to the examiner. In examining the differential impact of maltreatment subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
3
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 31 publications
17
170
3
10
Order By: Relevance
“…Macfie, Toth, Rogosch, Robinson, Emde, and Cicchetti (1999) reported that maltreated children displayed fewer representations of parental distress relief (i.e., parents' response to children's verbal or non-verbal cues for help or empathy) in narratives compared to nonmaltreated children. Furthermore, Toth, Cicchetti, Macfie, and Emde (1997) showed that maltreated and abused preschoolers were more likely to represent their parents negatively, as more controlling, and to have fewer positive and effective discipline representations during their story stem narratives. Taken together, these findings provide support for the penetrating effects of dysfunctional caregiving (e.g., maltreatment and/or abuse) early in life in relation to children's internal representations of their parents detectable through children's story stem narratives.…”
Section: Parenting Behaviors and Children's Representations Of Parentsmentioning
confidence: 99%
“…Macfie, Toth, Rogosch, Robinson, Emde, and Cicchetti (1999) reported that maltreated children displayed fewer representations of parental distress relief (i.e., parents' response to children's verbal or non-verbal cues for help or empathy) in narratives compared to nonmaltreated children. Furthermore, Toth, Cicchetti, Macfie, and Emde (1997) showed that maltreated and abused preschoolers were more likely to represent their parents negatively, as more controlling, and to have fewer positive and effective discipline representations during their story stem narratives. Taken together, these findings provide support for the penetrating effects of dysfunctional caregiving (e.g., maltreatment and/or abuse) early in life in relation to children's internal representations of their parents detectable through children's story stem narratives.…”
Section: Parenting Behaviors and Children's Representations Of Parentsmentioning
confidence: 99%
“…By four years old, children already display consistent individual differences in the quality and quantity of their negative emotional reaction in facing a failure (Alessandri and Lewis 1996;Dweck, Chiu and Hong 1995). Compared to the not maltreated ones, physically abused children, but not the neglected ones, have more negative representations of the self (Toth et al 1997) and are more likely to experience self-evaluative emotions in reaction to a failure, because of the biases in their negative beliefs about the self, their abilities and their personal value.…”
Section: The Role Of the Emotional Processesmentioning
confidence: 99%
“…When the sample of preschool children included greater diversity (43% African-American, 3% Latino, 18% mixed ethnic background) and older preschoolers (mean age of 5 years), their narratives contained more negative maternal and self-representations than did narratives of nonmaltreated children (Toth, Cicchetti, Macfie & Emde, 1997). These maltreated children also portrayed more grandiose self-representations, were less responsive to the examiner, and displayed fewer disciplining parent representations than nonmaltreated children.…”
Section: Maltreated Versus Non Maltreated Samplesmentioning
confidence: 99%
“…In the creation process, where parents and children construct narrative accounts of family experience, caretakers can contribute to children's rising levels of anxiety and confusion, oppositional, defiant, aggressive behavior, and other antisocial disorders, or they can instill an increasing awareness and ability to successfully cope with conflictual events and painful emotions (Slade, 1994). Representational research suggests that preschool children have the emotional capacity and cognitive maturity to inform us about their caregiving experiences (Toth et al, 1997).…”
Section: Caregiving and Early Risk For Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation